Walking the Talk? An Examination of the Investments of Jesuit Universities in Fossil Fuel Firms - Kimbro, Marinilka Barros (Archīum Ateneo, 2023)
This article investigates perspectives that have been proposed as reasons both for and against fossil fuel divestment (FFD), paying special attention to the decisions that universities make concerning investments in their endowment portfolios. Arguments that have been advanced against FFD include its supposedly lower financial returns, lack of direct control over investments, reliance on financial advisors, high transaction costs, the need for market index funds that include the stocks of fossil fuel firms, and the institution’s fiduciary duty to increase returns. Arguments that have been advanced in favor of FFD include satisfactory returns from fossil fuel-free portfolios, risk reduction, the over-pricing of fossil fuel firms, improved portfolio diversification, and the need to align investing behavior with the institution’s values, mission, and role in society. The study challenges the alleged financial reasons for maintaining investments in fossil fuel firms by presenting evidence that divestment does not impair portfolio performance on a risk-adjusted basis, nor does it increase long-term transaction costs. Fossil fuel firms are overvalued given that they will eventually suffer from the increasing demand for clean energy substitutes and face inevitable regulatory actions as the effects of climate change worsen. Divestment, therefore, might well provide higher risk-adjusted returns over the long-term.